MANAGEMENT OF HYPERTENSION IN A 75-YEAR-OLD FEMALE PATIENT THROUGH A FAMILY MEDICINE APPROACH AT MUARA BATU PRIMARY HEALTH CENTER, NORTH ACEH REGENCY - M. Doli Reza Lubis (Jurnal Medika Hutama, 2026)
A 75-year-old female patient, Mrs. F, presented to the geriatric clinic at Muara Batu Primary Health Center with a chief complaint of headache for the past two days. The headache was predominantly located in the occipital region, described as a tightening sensation and occasionally throbbing in nature, intermittent, and of moderate intensity, often occurring during physical activity. The complaint was not accompanied by dizziness. The patient also reported pain and a sensation of heaviness in the nuchal region, along with neck stiffness. Additionally, she complained of pain in both legs during physical activity. The patient had been diagnosed with hypertension for the past 10 years and had been prescribed amlodipine 10 mg/day; however, she was non-adherent to the medication regimen. Primary data were obtained through autoanamnesis and physical examination during a home visit, along with documentation in the family folder and patient records. Assessment was conducted based on initial, process, and final holistic diagnoses using both quantitative and qualitative approaches. Interventions included providing education to the family regarding hypertension, lifestyle modification, and disease management, as well as explaining potential complications to improve treatment adherence and encourage preventive measures.